STRATEGI MARKETING PUBLIC RELATIONS DINAS PARIWISATA DAN KEBUDAYAAN KOTA BOGOR DALAM MEMPERKENALKAN BATIK BOGOR - Sinta Devi Lestari; Sardi Duryatmo; Prasetyo Adinugroho (UNIVERSITAS PAKUAN, 2021)
The purpose of this study was to determine the analysis of the marketing public relations department of tourism and culture of the city of Bogor in introducing Batik Bogor. This research has a problem formulation that is not well known Bogor batik by the public, especially the Bogor community itself. In that addition to knowing the supporting factors and inhibiting factors in introducing Batik Bogor. in this study the research method used was descriptive qualitative form of written or oral words from people and the observed behavior in obtaining data used interviews, observation, and documentation. The theory used in this study is the marketing public relations and the key informant is Undang Sulaeman as the partnership and creative economy developmeint section and Sri Hartati as Bogor batik craftsman.